Flame retardant and mechanically tough poly(lactic acid) biocomposites via combining ammonia polyphosphate and polyethylene glycol. (December 2017) - Sun, Yiqi; Sun, Shuai; Chen, Lei; Liu, Lina; Song, Pingan; Li, Wei; Yu, Youming; Fengzhu, Lu; Qian, Jun; Wang, Hao
Abstract: Although the flammability of biodegradable poly(lactic acid) (PLA) has been effectively addressed so far, the resultant flame retardant PLA still displays a high brittleness, extremely restricting its wide applications in electrical, automobile and aerospace fields. In this work, we have demonstrated the fabrication of flame retardant and tough PLA composites by combining ammonia polyphosphate (APP) and poly(ethylene glycol) (PEG) with a molecular weight of 20, 000 via the melt-blending strategy. The results show that the peak heat release rate of PLA can reduce by 14% in cone tests and a V-0 rating is achieved in vertical burning tests by adding 7 wt% of APP and 14 wt% PEG. Moreover, such PLA composite shows a high strain at break of 280% and impact strength of 14.9 kJ/m 2, respectively increasing by thirty-eight-fold and two-fold relative to the PLA bulk. The results strongly indicate that flammability and brittleness of the PLA are strikingly reduced. This work provides an integrated strategy for creating advanced green polymer composites with exceptional flame resistance and toughness. Graphical abstract: Highlights: The flammability of polylactide (PLA) is dramatically reduced by adding ammonia polyphosphate and poly (ethylene glycol)-20000. The flame-retardant PLA composites display a high strain at failure of 280% and high impact strength of around 14.9 kJ/m 2 . This work provides a facile approach for creating flame-retardant and mechanically tough polymer composites.